2013
DOI: 10.1186/1472-6963-13-37
|View full text |Cite
|
Sign up to set email alerts
|

Direct economic burden of hepatitis B virus related diseases: evidence from Shandong, China

Abstract: BackgroundAlthough the expenses of liver cirrhosis are covered by a critical illness fund under the current health insurance program in China, the economic burden associated with hepatitis B virus (HBV) related diseases is not well addressed. In order to provide evidence to address the economic disease burden of HBV, we conducted a survey to investigate the direct economic burden of acute and chronic hepatitis B, cirrhosis and liver cancer caused by HBV-related disease.MethodsFrom April 2010 to November 2010, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 7 publications
0
48
1
Order By: Relevance
“…It means 0.7% population aged 18–74 years old in Henan, about 0.46 million people, may be had active HBV DNA replication. According to the survey of Jingjing Lu in 2013 [Lu et al, ], the directed economic disease burden may be met to 2.1 billion dollars in the future in Henan for treating the clinical Hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…It means 0.7% population aged 18–74 years old in Henan, about 0.46 million people, may be had active HBV DNA replication. According to the survey of Jingjing Lu in 2013 [Lu et al, ], the directed economic disease burden may be met to 2.1 billion dollars in the future in Henan for treating the clinical Hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have been conducted included hospitalized patients, and little information is available on the community‐based estimation of NAFLD burden. In low‐income countries like Bangladesh, hospital‐based prevalence estimates may underestimate the true burden of disease as many patients with NAFLD may never seek medical care as a result of being asymptomatic, having limited access to healthcare services, and being in fear of significant economic burden …”
Section: Introductionmentioning
confidence: 99%
“…3 In a study of the economic burden of chronic hepatitis B in Beijing and Guangzhou, 4 Hu and Chen found the disease imposed a 'substantial economic burden on patients, families and the society in China urban areas'. In Shandong province, Lu et al estimated the in-patient costs of hepatitis B-related diseases ranged from $US2954 to $US10635 per patient, 5 and Zhang et al found that in Jiangsu province the direct economic costs of HBV-related diseases ranged from $US107 for out-patients to $US3193 for in-patients. 6 All these studies advocated the need for public health officials to intervene to reduce HBV-related diseases.…”
Section: Introductionmentioning
confidence: 99%